ANALISA KARAKTERISTIK MANISAN KERING SALAK(SALACCA EDULIS) DENGAN LAMA PERENDAMAN DAN KONSENTRASI LARUTAN GULA - Arini Maulidiah; Darimiyya Hidayati; Sri Hastuti (AGROINTEK, 2014)
Snake fruit (Salacca edulis) can be made into dried fruit with addition of high concentration of sugar syrup prior to drying. This study aims to determine the effect of the concentration of sugar solution and soaking time on the characteristics of candied snake fruit. The experimental design used was a completely randomized design (CRD) factorial consisting of two factors: the concentration of sugar solution (40%, 50%, 60%) and the soaking time (24 and 48 hours). Each treatment was repeated three times. Data processing on quality of candied snake fruit was done using the General Linear Model (GLM) and univariate test of Duncan Multiple Range Test (DMRT). Results showed that concentration of sugar solution and soaking time gave significant effect on concentration of reducing sugar. Soaking at 48 hours significantly affectedyield, preferences for taste, texture, and overall preferences of candied snake fruit. Interaction of soaking and the concentration of sugar solution significantly affected moisture content of final product.